Severe sepsis in women with group B Streptococcus in pregnancy: an exploratory UK national case–control study. Issue 10 (8th October 2015) - Kalin, Asli; Acosta, Colleen; Kurinczuk, Jennifer J; Brocklehurst, Peter; Knight, Marian
Abstract : Objective: To estimate the incidence of severe maternal sepsis due to group B Streptococcus (GBS) in the UK, and to investigate the associated outcomes for mother and infant. Design: National case–control study. Setting: All UK consultant-led maternity units. Participants: 30 women with confirmed or suspected severe GBS sepsis, and 757 control women. Main outcome measures: Disease incidence, additional maternal morbidity, critical care admission, length of stay, infant infection, mortality. Results: The incidences of confirmed and presumed severe maternal GBS sepsis were 1.00 and 2.75 per 100 000 maternities, respectively, giving an overall incidence of 3.75 per 100 000. Compared with controls, severe GBS sepsis was associated with higher odds of additional maternal morbidity (OR 12.35, 95% CI 3.96 to 35.0), requiring level 2 (OR 39.3, 95% CI 16.0 to 99.3) or level 3 (OR 182, 95% CI 21.0 to 8701) care and longer hospital stay (median stay in cases and controls was 7 days (range 3–29 days) and 2 days (range 0–16 days), respectively, p<0.001). None of the women died. Severe maternal GBS sepsis was associated with higher odds of infant sepsis (OR 32.7, 95% CI 8.99 to 119.0); 79% of infants, however, did not develop sepsis. There were no associated stillbirths or neonatal deaths. Conclusions: Severe maternal GBS sepsis is a rare occurrence in the UK. It is associated with adverse maternal and neonatal outcomes.